Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

Bentonite - Clay - supported cuprous iodide nanoparticles (BENT- CuI NPs): a new heterogeneous catalyst in diversity - oriented synthesis of 1, 2, 3-triazoles in aqueous medium - Chavan, V, Pramod; Charate, Shrinivas P.; Desai, V, Uday; Rode, V, Chandrashekhar; Wadgaonkar, Prakash P. (Chemistryselect, 2019)
Bentonite clay supported cuprous iodide nanoparticles (BENT-CuI NPs) were prepared and demonstrated for the first time as an efficient heterogeneous catalyst in diversity oriented, green synthesis of 1,2,3-triazoles by one-pot, three component reaction between alkyl halides, arylboronic acids, or epoxides with alkynes and sodium azide in aqueous medium. The catalyst was characterized by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Energy Dispersive X-ray Spectroscopy(EDS), Scanning Electron Microscopy (SEM), X-Ray Powder Diffraction (XRD), Transmission Electron Microscopy (TEM) as well as Brunauer-Emmett-Teller (BET) techniques and was found to be reusable for five consecutive runs without significant loss of activity.
Keywords: 1; 2; 3-triazoles; arylboronic acids; click synthesis; epoxides; green chemistry; heterogeneous catalyst

Kinetics of hydrogenation of aqueous levulinic acid over bimetallic Ru-Ni/MMT catalyst - Kasar, Gayatri B.; Medhekar, Rucha S.; Bhosale, P. N.; Rode, V, Chandrashekhar (Industrial & Engineering Chemistry Research, 2019)
gamma-Valerolactone is one of the value-added products obtained from levulinic acid hydrogenation, having tremendous applications in fuels and chemicals. In this work, several monometallic and bimetallic compositions of Ru and Ni were prepared and evaluated for levulinic acid hydrogenation in an aqueous medium. The optimum composition of 0.5 wt % Ru and 5 wt % Ni on MMT was found to achieve 91% levulinic acid conversion with complete selectivity to gamma-valerolactone within 5 h at 220 degrees C and 250 psig H-2 pressure. XPS and H-2-TPR studies clearly showed that the electronic interactions between Ru-Ni leading to the synergism enhanced the catalytic efficiency of the Ru-Ni bimetallic catalyst. The average metal particle size by HRTEM was found to be in the range of 1.5-4.5 nm, having mixed cubic, oval, and spherical morphology, dispersed on the surface as well as within the layers of MMT. NH3-TPD showed a higher acidity due to both Lewis and Bronsted sites of the 0.5 wt % Ru-5 wt % Ni/MMT catalyst than individual MMT and monometallic catalysts. The presence of higher Lewis acidic sites preferred selective formation of GVL. Reaction kinetics was studied to propose the rate equation for this reaction based on which a plausible reaction pathway is proposed involving a first step dehydration of levulinic acid to an alpha-angelica lactone intermediate which then undergoes hydrogenation by dissociatively adsorbed H-2 to form gamma-valerolactone. The stability of our catalyst was proved by its recycle studies as well as by a hot filtration test.

Enolate-mediated regioselective synthesis of 1,2,3-triazoles via azide-aldehydes or ketones [3+2]-cycloaddition reactions in aqueous phase - Tripathi, Anupam; Rode, V, Chandrashekhar; Llop, Jordi; Chavan, Subhash P.; Joshi, Sameer M. (Tetrahedron Letters, 2020)
A synthetic route for the direct conversion of arylazides into the corresponding trizoles via phase transfer catalyst-assisted [3+2] cycloaddition reaction under basic conditions in aqueous medium is reported. This synthetic methodology, which offers high yields and excellent regioselectivity for varieties of triazoles at 100 degrees C for 24 h-48 h and this `greener' synthesis constitutes an alternative to the previously reported well established click reactions. Published by Elsevier Ltd.
Keywords: Azides plus aldehydes or ketones; Click chemistry; triazoles; Water

Rational synthesis of 10GDC electrolyte through a microwave irradiation GNP facile route for SOFC applications - Shaikh, S. P. S.; Rode, V, Chandrashekhar (RSC Advances, 2020)
The gadolinium-doped ceria Gd0.1Ce0.9O1.95 (10GDC) powder was synthesized using a microwave-synthesized glycine nitrate process (MS-GNP). The powder was subsequently pressed into circular pellets and sintered at various temperatures viz. 800, 900, 1000 and 1200 degrees C, in a microwave, high temperature furnace for 4 h so as to investigate the effect of the sintering temperature and sintering environment on the structural, morphological, thermal and electrical properties. The crystallite size and particle size as observed from X-Ray Diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) are found to be in the range of 15-28 nm and 12-20 nm, respectively. The electrochemical impedance spectroscopy (EIS) analysis was carried out to study the electrochemical properties during the cooling cycle from 400 degrees C to 800 degrees C. The highest value of ionic conductivity (3.55 x 10(-1) S cm(-1)) is observed at an operating temperature of 800 degrees C and O-2 gas partial pressure of 1 atm. Further, it is observed that the sintering temperature has a significant effect on the surface morphology and crystallite size, thereby improving the electrical performance of the samples. Though 20GDC was used as an electrolyte in the authors' previous study, the novelty of the present work is the synthesis of 10GDC using a microwave-assisted glycine nitrate process and the size (thickness) of the prepared electrolyte for use in a Solid Oxide Fuel Cell (SOFC), which plays a major role in enhancing the structural, morphological and electrochemical properties with respect to different sintering temperatures as compared to the reported data. Hence, the prepared 10GDC electrolyte may be treated as one of the promising candidates as an electrolyte for SOFC for intermediate as well as high temperature applications.

Synthesis and characterization of supported heteropoly acid: efficient solid acid catalyst for glycerol esterification to produce biofuel additives - Magar, Subhash; Mohanraj, Govindraj T.; Jana, Sumit Kumar; Rode, V, Chandrashekhar (Inorganic and Nano-Metal Chemistry, 2020)
Esterification of glycerol with acetic acid has been studied with different solid acid catalysts, prepared by impregnating phospotungustic, silicotungstic, and phosphomolybdic acids on polymeric material polyvinylpyrrolidone. These results were compared with commercially available montmorillonite KSFO catalyst showed that PVP-DTP gave higher selectivity to di- and triacetins. This study was mainly focused on increasing the selectivity toward triacetin which is an excellent alternative to fossil fuel based fuel additives. The detail characterization was done for the PVP-DTP catalyst which gave complete conversion of glycerol and maximum selectivity of 34% toward triacetin. Complete conversion of glycerol was achieved at 110 degrees C within 6 h of reaction time. The characterization of the catalyst was performed by SEM/EDX, X-ray diffraction, thermogravimetic techniques, and FT-IR analysis.TPD-NH3 characterization showed that DTP supported on PVP increases the catalyst acidity of PVP. The highest acidity of PVP-DTP is also confirmed using NH3-TPD analysis.
Keywords: Glycerol; phospostugustic acid; povidone; solid acid catalyst; triacetin

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies

Hydrogenolysis of benzofuran using aqueous ethanol solution over graphite-supported platinum catalyst - Hiraishi, Yushi; Minakawa, Naohiro; Taniguchi, Kenkichi; Nagasawa, Yoshiyuki; Nanao, Hidetaka; Rode, V, Chandrashekhar; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (Journal of the Indian Chemical Society, 2021)
Graphite-supported platinum catalysts (Pt/G) were highly active for the hydrogenolysis of benzofuran to o-ethylphenol in aqueous ethanol solution at 523 K without using any external hydrogen gas. The hydrogenolysis activities and selectivity to o-ethylphenol in ethanol solution over Pt/G were higher than those with a conventional method using externally supplied hydrogen gas. Both water and ethanol were indispensable for the hydrogenolysis in aqueous ethanol solution at 523 K.
Keywords: Biomass conversion; Graphite support; Hydrogenolysis; platinum catalysts

Activity performance and kinetics for glycerol carbonylation with urea over Zn-Co mixed metal oxide catalyst - Kondawar, Sharda E.; Kasar, Gaytri B.; Khatua, Angshuman S.; Rode, V, Chandrashekhar (Canadian Journal of Chemical Engineering, 2023)
Efficient carbonylation of glycerol using urea with Zn-Co mixed metal oxide (MMO) catalyst has been achieved. Various methods of catalyst preparation were explored for glycerol carbonate (GC) synthesis. The optimized method of catalyst preparation was found to be co-precipitation (CP) with a Zn:Co ratio of 70:30, achieving 81% glycerol conversion with 97% GC selectivity. X-ray diffraction (XRD) studies revealed the formation of ZnO, Co-3 O-4, and spinel ZnCo2O4 phases. Thermal treatment given to the catalyst allows insertion of Zn cations into Co3O4 lattice forming ZnCo2O4 phase which was also evidenced in X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. Herein, for the first time, reaction kinetics was studied to propose the rate equation, based on which a plausible reaction pathway is proposed involving two-site adsorption of glycerol (basic site) and urea (acidic site), which undergo carbonylation followed by cyclization into GC. A recycle study and hot filtration test have proven the reusability of the catalyst.
Keywords: Carbonylation; cyclic carbonate; Glycerol; kinetics; mixed metal oxide